Rumen fermentation and rumen microbes in Nellore steers receiving diets with different lipid contents - Messana, Juliana Duarte [UNESP]; Berchielli, Telma Teresinha [UNESP]; Arcuri, Pedro Braga; Reis, Ricardo Andrade [UNESP]; Canesin, Roberta Carrilho [UNESP]; Ribeiro, Andressa Ferreira [UNESP]; Fiorentini, Giovani [UNESP]; Fernandes, Juliano José de Resende (Sociedade Brasileira de Zootecnia, 2013)
The objective of the present study was to evaluate the effects of dietary lipid content (20, 40 and 60 g/kg dry matter) on intake, total and ruminal apparent digestibility of dry matter (DM), nutrient digestibility, rumen fermentation parameters, microbial synthesis efficiency and rumen microbial content of beef cattle. Nine cannulated steers at 6 months of age with initial body weight of 232±35 kg were used in a triplicate 3 × 3 Latin square design. The results indicated that the total intake and digestibility of DM, organic matter (OM), gross energy (GE), neutral detergent fiber (NDF) and acid detergent fiber (ADF) were not affected by the lipid content of the diet. However, the lowest lipid content diet reduced the total digestibility of crude protein (CP) and total carbohydrate linearly compared with the highest lipid diet. In contrast, when steers were fed a diet containing 20 g lipids/kg of DM, the concentration of ammonia in the rumen decreased quadratically relative to the other diets. Ruminal pH was not affected by the interaction of treatment and sampling time; however, the rumen pH decreased quadratically in animals that received the highest dietary lipid content (60 g/kg) compared with animals that received 20 and 40 g lipids/kg of DM. The rumen concentrations of volatile fatty acids, propionate, and butyrate and the acetate/propionate ratio were affected by the dietary lipid content. However, the microbial population, microbial N flow, and efficiency of synthesis were not affected by dietary lipid content. Overall, an increase in the lipid content of the diet of Nellore steers resulted in similar digestive profiles and fermentation conditions.
Keywords: Bovines; Digestibility; Fat; Soybean; volatile fatty acids